2017
DOI: 10.1155/2017/9474896
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Alters Gut Microbiota and the Expression of Paneth Cell-Antimicrobial Peptides Preceding Changes of Circulating Inflammatory Cytokines

Abstract: Obesity is an established risk factor for many diseases including intestinal cancer. One of the responsible mechanisms is the chronic inflammation driven by obesity. However, it remains to be defined whether diet-induced obesity exacerbates the intestinal inflammatory status by cytokines produced in adipose tissue or the high fat diet first alters the gut microbiota and then drives intestinal inflammation. To address this question, we fed C57BL/6 mice with a high fat diet (HF, 60%) and sacrificed them sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 40 publications
10
102
2
2
Order By: Relevance
“…Additionally, fetuses from HF mothers showed an increase in gut mRNA expression levels of AMP genes Lyz1 (but not Lyz2), Defa1, and Reg3g. This is in contrast to studies in adult mice (35,40,60,70) that have demonstrated that HF diets decrease gut levels of AMPs, though one study (37) found differing results between the mRNA and protein levels. Nevertheless, our study is the first to our knowledge to uncover how maternal malnutrition alters expression levels of AMPs in near-term fetuses and is the first to assess Reg3g mRNA expression in fetal tissues.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Additionally, fetuses from HF mothers showed an increase in gut mRNA expression levels of AMP genes Lyz1 (but not Lyz2), Defa1, and Reg3g. This is in contrast to studies in adult mice (35,40,60,70) that have demonstrated that HF diets decrease gut levels of AMPs, though one study (37) found differing results between the mRNA and protein levels. Nevertheless, our study is the first to our knowledge to uncover how maternal malnutrition alters expression levels of AMPs in near-term fetuses and is the first to assess Reg3g mRNA expression in fetal tissues.…”
Section: Discussioncontrasting
confidence: 79%
“…Extensive research has demonstrated that high-fat diets markedly alter the diversity and composition of gut microbes (40,(60)(61)(62)(63)(64), resulting in long-term aberrations in gut barrier integrity (40,(60)(61)(62)65) and function (40,60,66) and chronic inflammation (40,61,62). As a result, we hypothesised that mothers fed a HF diet would show pronounced changes in gut function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As anticipated, HFD increased the level of aortic ROS, serum leptin and resistin, which further prompted aortic tissue maladaptive immune response and release of proinflammatory cytokines, including MCP1, IL6 and IL8. It has been demonstrated that HFD and high-fructose beverages increased body weight, leptin, inflammation and insulin resistance that are associated with steatosis, and oxidative stress in plasma and tissues, indicating that oxidative stress and inflammation are important contributors to the pathogenesis of CVD (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…This is known as the entero-mammary pathway. At least 200 bacterial species have been isolated from human milk but the great diversity is linked to the variations in the culture methods or geographical differences (Li et al, 2017). Bacteria from the phylum Proteobacteria, Firmicutes (Pannaraj et al, 2017), and Bifidobacteria have been found in human milk (Cabrera-Rubio, Mira-Pascual, Mira, & Collado, 2016).…”
Section: Microbial Colonizationmentioning
confidence: 99%